2019
DOI: 10.3390/ma12223657
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetry and Mass Spectrometry of Extractable Organics from Manufactured Nanomaterials for Identification of Potential Coating Components

Abstract: Manufactured nanomaterials (MNMs) often have a surface-chemical modification in order to tailor their physicochemical properties, including also powder properties and miscibility. Surface-chemical modifications may influence the toxicological properties of the MNM, but the specific chemistry and extent are rarely described in detail in suppliers’ technical data sheets. Chemical and quantitative information on any surface-chemical treatment, coating and functionalization are required for chemicals registration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 57 publications
3
12
1
Order By: Relevance
“…The present study illustrates the extent of optimization that may be needed for accurate determination of the content of functional groups or coatings and identification of impurities. These results also provide some insight into probable causes for the discrepancies between TGA and MS noted in the previous study [4].…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…The present study illustrates the extent of optimization that may be needed for accurate determination of the content of functional groups or coatings and identification of impurities. These results also provide some insight into probable causes for the discrepancies between TGA and MS noted in the previous study [4].…”
Section: Discussionsupporting
confidence: 58%
“…The above study [4] also examined sample JRC-02-C8 and reported a mass loss of 2.1% from TGA; only 10% of this could be accounted for by the trimethoxyalkylsilane detected by MS after solvent extraction [4]. This product was hypothesized to be derived from reaction of the initial silane at the temperature used for solvent extraction.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Characterization of carbon black (Jacobsen et al 2007(Jacobsen et al , 2008(Jacobsen et al , 2011 and the Bentonite (Jensen et al 2009) used in this study have previously been published. Furthermore, full thermo-gravimetric analysis (TGA) of the four ONC is available (Clausen et al 2019).…”
Section: Characterization Of Particlesmentioning
confidence: 99%